Sport-Related Structural Brain Injury and Return to Play: Systematic Review and Expert Insight. Issue 6 (8th June 2021) - Zuckerman, Scott L; Yengo-Kahn, Aaron M; Tang, Alan R; Bailes, Julian E; Beauchamp, Kathryn; Berger, Mitchel S; Bonfield, Christopher M; Camarata, Paul J; Cantu, Robert C; Davis, Gavin A; Ellenbogen, Richard G; Ellis, Michael J; et al.
Abstract: BACKGROUND: Sport-related structural brain injury (SRSBI) is intracranial pathology incurred during sport. Management mirrors that of non-sport-related brain injury. An empirical vacuum exists regarding return to play (RTP) following SRSBI. OBJECTIVE: To provide key insight for operative management and RTP following SRSBI using a (1) focused systematic review and (2) survey of expert opinions. METHODS: A systematic literature review of SRSBI from 2012 to present in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and a cross-sectional survey of RTP in SRSBI by 31 international neurosurgeons was conducted. RESULTS: Of 27 included articles out of 241 systematically reviewed, 9 (33.0%) case reports provided RTP information for 12 athletes. To assess expert opinion, 31 of 32 neurosurgeons (96.9%) provided survey responses. For acute, asymptomatic SRSBI, 12 (38.7%) would not operate. Of the 19 (61.3%) who would operate, midline shift (63.2%) and hemorrhage size > 10 mm (52.6%) were the most common indications. Following SRSBI with resolved hemorrhage, with or without burr holes, the majority of experts (>75%) allowed RTP to high-contact/collision sports at 6 to 12 mo. Approximately 80% of experts did not endorse RTP to high-contact/collision sports for athletes with persistent hemorrhage. Following craniotomy for SRSBI, 40% to 50% of experts considered RTP at 6 to 12 mo. Linear regression revealed that experts allowed earlier RTP at higher levels of play (β = –0.58, 95% CI –0.111, –0.005, P = .033). CONCLUSION: RTP decisions following structural brain injury in athletes are markedly heterogeneous. While individualized RTP decisions are critical, aggregated expert opinions from 31 international sports neurosurgeons provide key insight. Level of play was found to be an important consideration in RTP determinations.